Effects of Contact Angle and Flocculation of Particles of Oligomer of Tetrafluoroethylene on Oil Foaming - Murakami, Ryo; Kobayashi, Syuji; Okazaki, Manami; Bismarck, Alexander; Yamamoto, Masahiro (Frontiers in Chemistry, 2018)
Oil foams have been stabilized by using particles of oligomer of tetrafluoroethylene (OTFE). OTFE particles were dispersed in oil mixtures prior to aeration, to exclude the oil-repellency nature of the particles due to the formation of the metastable Cassie-Baxter state and properly evaluate the effects of contact angle on the foaming behavior. The particle contact angle (θY) against air/oil surfaces were controlled by changing a composition of two oils with different surface tension (n-heptane and methyl salicylate). The θY value increases with increasing a mole fraction of methyl salicylate, from 42º (for pure n-heptane) to 89º (for pure methyl salicylate). The air volume incorporated in the oils after aerating OTFE dispersions in the oil mixtures shows a maximum when θY = 55º. The flocculation of OTFE particles in bulk oils is responsible for the unexpected behavior of foaming observed when θY is relatively high. The increase in the degree of the flocculation reduces the effective concentration of OTFE particles in bulk oil, leading to the inefficient bubble stabilization. These findings suggest the efficient oil foaming using particles as a stabilizer is achieved by optimizing both the particle contact angle and the degree of flocculation in oils.